Functional analysis of two SfHsp90 genes in response to high temperature and insecticide stress in Spodoptera frugiperda (Lepidoptera: Noctuidae) - RUAN, Hong-Yun; ZHOU, Lv; YANG, Lei; MENG, Jian-Yu; ZHANG, Chang-Yu (European journal of entomology, 2024)
Spodoptera frugiperda, a worldwide pest, can feed on 353 crops species, including corn, rice, and sorghum. It is highly adaptable to various environments. Heat shock protein 90 kDa (Hsp90) plays a crucial role in the environmental adaptation of insects. To explore the role of SfHsp90 genes coding for Hsp90 proteins in the high temperature and insecticides stress resistance of Spodoptera frugiperda, we identified the complete complementary DNA sequences of two SfHsp90s. Both of them were expressed at different developmental stages and tissues in S. frugiperda. The expression levels of the SfHsp90s were significantly upregulated when exposed to durations of extreme temperature (45°C) and lethal concentrations of emamectin benzoate (LC10 and LC20). The viability of S. frugiperda under 45°C and emamectin benzoate stresses was examined. The mortality rate of S. frugiperda was significantly increased when subjected to 45°C and emamectin benzoate after knockdown of SfHsp90s by RNAİ. These results suggest that SfHsp90s are essential for the resistance of S. frugiperda to high temperature and emamectin benzoate stresses.